How the race to achieve Aichi Target 11 could jeopardize the effective conservation of biodiversity in Canada and beyond. (January 2019) - Lemieux, Christopher J.; Gray, Paul A.; Devillers, Rodolphe; Wright, Pamela A.; Dearden, Philip; Halpenny, Elizabeth A.; Groulx, Mark; Beechey, Thomas J.; Beazley, Karen
Abstract: In 2010 Parties to the United Nations (UN) Convention on Biological Diversity (CBD) agreed to reduce the rate of biodiversity loss within a decade by achieving 20 objectives that are commonly known as the Aichi Targets. This article explores aspects of Canada's work on one of the few quantified targets (Target 11), which is intended to improve the status of biodiversity through protected areas (PAs) and a new type of designation, "other effective area-based conservation measures" (OECMs). In a faltering attempt to reach its Aichi Target 11 commitments by 2020, some Canadian jurisdictions have elected to focus more on coverage (quantity) and less on ecological integrity (quality), which has significant ramifications for long-term success of biodiversity conservation. For example, a jurisdiction responsible for marine conservation has re-designated regulated fishery closures as 'marine refuges' under the auspices of an OECM designation, which brings into question the real intent of Canada's commitment to the CBD and its own Biodiversity Strategy. Ambiguous language used to define and prescribe application of OECMs is being used as the basis for a revisionist paradigm that promises to undermine national and international conservation standards, fracture partnerships, and jeopardize the integrity of Canada's PA network. Canada must reject half measures that will result in ineffective or unintended perverse conservation outcomes, and focus on a post-2020 agenda that prioritizes conservation outcomes, management effectiveness, and the implementation of accountability measures within and between jurisdictions and by the Secretariat of the CBD. Highlights: Practitioners/scholars warned about the potential risks to effective biodiversity conservation associated with Aichi Target 11. In Canada, recently established, 'marine refuges' do little to mitigate the increasing risks to ocean ecosystems. Focusing on quantity over quality of protection jeopardizes biodiversity conservation. Canada should focus on biodiversity outcomes under its post-2020 conservation agenda outcomes. Enhanced accountability in Canada and also by the Secretariat of the CBD is required.